2013
DOI: 10.1364/oe.21.019608
|View full text |Cite
|
Sign up to set email alerts
|

Fundamentally mode-locked, femtosecond waveguide oscillators with multi-gigahertz repetition frequencies up to 15 GHz

Abstract: Abstract:We demonstrate passively mode-locked Yb 3+ -doped glass waveguide lasers in a quasi-monolithic configuration with a maximum pulse repetition frequency up to 15.2 GHz. A semiconductor saturable absorber mirror (SESAM) is used to achieve stable mode-locking around 1050 nm with pulse durations as short as 811 fs and an average power up to 27 mW. Different waveguide samples are also employed to deliver pulses with repetition rates of 4.9 GHz, 10.4 GHz and 12 GHz with an average power of 32 mW, 60 mW and 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…Indeed, mode-locked waveguide lasers have been demonstrated using SESAMs [9][10][11][12], obtaining a repetition rate as high as 15 GHz [10] from an integrated ion-exchanged waveguide laser. Ionexchange is a versatile technique for producing low-loss waveguides and is compatible with photonic mass-production techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, mode-locked waveguide lasers have been demonstrated using SESAMs [9][10][11][12], obtaining a repetition rate as high as 15 GHz [10] from an integrated ion-exchanged waveguide laser. Ionexchange is a versatile technique for producing low-loss waveguides and is compatible with photonic mass-production techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Later work by R. Mary demonstrated a Q-switched modelocked laser with Yb:BG waveguides using a graphene saturable output coupler with a PRF of 1.5 GHz [6]. Lagatsky et al [7] reported that group velocity dispersion (GVD) can be controlled by accurately changing the length of the gap between the end facet of the waveguide and one of the cavity mirrors. This method of the GVD control was used to demonstrate a fundamentally mode-locked femtosecond laser in Yb:IOG-1 with a PRF of 15.2 GHz and pulse energy of 1.8 pJ [7].…”
Section: Introductionmentioning
confidence: 99%
“…Lagatsky et al [7] reported that group velocity dispersion (GVD) can be controlled by accurately changing the length of the gap between the end facet of the waveguide and one of the cavity mirrors. This method of the GVD control was used to demonstrate a fundamentally mode-locked femtosecond laser in Yb:IOG-1 with a PRF of 15.2 GHz and pulse energy of 1.8 pJ [7]. By combining the work of R. Mary and A.…”
Section: Introductionmentioning
confidence: 99%
“…Other advantages include a low laser and mode-locking threshold owing to the small mode sizes and a thin-slab configuration allowing good thermal management which is advantageous for power scaling. Recently, several mode-locked waveguide laser systems have been demonstrated [1][2][3] in the 1-1.5 m spectral window using semiconductor saturable absorber mirrors (SESAMs) with repetition rates as high as 15 GHz [2] being achieved. However, SESAM fabrication can be relatively expensive and the resulting bandwidth of operation of the device is quite limited. Graphene has recently emerged as an interesting alternative for use as a saturable absorber [4] and has the advantage of having a wide wavelength band of operation and being easy and relatively low-cost to fabricate.…”
Section: Introductionmentioning
confidence: 99%